Systematic Literature Review: The Role of Artificial Intelligence in Digital Marketing - Yusup, Muhamad; Wijono, Sutarto; Manongga, Danny; Sembiring, Irwan; Prasetyo, Sri Yulianto Joko; Wellem, Theophilus (Journal Sensi: Strategic of Education in Information System, 2024)
Artificial Intelligence has given a competitive advantage and can increment competition and benefit or Return on Venture in Computerized Showcasing. This article points to recognize diary sources related to the part of Fake Insights, explanatory strategies, applicabilities, and execution measurements on the part of AI in Computerized Promoting from 2015 to 2022. Based on the incorporation and prohibition criteria outlined, it was established that 8 things related to the article were distributed in 2015 and 2022. This article is organized utilizing the SLR strategy which is characterized as a preparation for recognizing, evaluating and evaluating the all accessible investigation to supply answers to four Research Questions. With Suggestions, and add up to of eleven investigation strategies, seventeen usage and nine execution measurements have been distinguished that can be utilized by analysts for future inquire about the part of Manufactured Insights in Computerized Promoting.